The Effect of Digital Technology Use on Employee Productivity through Work Stress as a Mediating Variable - Salim Setiawan; Nurul Hayat; Desi Rubiyanti (Advances in Community Services Research, 2026)
Purpose: This study aims to examine the effect of digital technology use on employee productivity, with work stress acting as a mediating variable at the Kelurahan Offices in Dompu District. Research Method: This quantitative research utilized a sample of 77 employees from six kelurahan offices. Data were collected via questionnaires and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. Results and Discussion: The analysis shows that digital technology use has a positive, significant direct effect on employee productivity, while simultaneously increasing work stress. Furthermore, work stress directly affects productivity and serves as a mediating variable that bridges the relationship between digital technology and employee productivity. Implications: The dynamics of productivity improvement due to digital technology are highly influenced by the work stress experienced during adaptation. Relevant institutions should conduct periodic technology training and adjust workloads to minimize adaptation tension (technostress). Originality: This research uniquely highlights the dual-edged impact of digitalization within the specific context of local government administration, providing empirical evidence on technostress as a crucial mediator.